Validation of GLIM criteria for hospital malnutrition diagnosis by comparison of three different anthropometric approaches to evaluate reduced muscle mass: a prospective cohort study - Jazinaki, Mostafa Shahraki; Safarian, Mohammad; Arabi, Seyyed Mostafa; Jamali, Jamshid; Norouzy, Abdolreza (Frontiers in Nutrition, 2024)
Background & Aims: The Global Leadership Initiative on Malnutrition (GLIM) recently proposed a new malnutrition diagnostic tool known as the GLIM criteria. The GLIM criteria need confirmed validation before being widely used in each population or healthcare system. This study aimed to investigate the validation of the GLIM criteria for malnutrition diagnosis in hospitalized patients. Methods: The content validity was assessed by calculating the content validity ratio (CVR) and content validity index (CVI). Subjective Global Assessment (SGA) is considered the reference tool to diagnose malnutrition in concurrent validation. Also, the Kudder-Richardson 20 was used to evaluate the reliability of the GLIM criteria. Furthermore, hospital mortality, length of hospitalization (LOS), prolonged hospital stays (LOS >6 days), 30-days hospital readmission, and 30- and 60-days mortality were identified as malnutrition-related outcomes in predictive validity. Results: A total of 332 adult/elderly hospitalized patients (median age: 58 (IQR: 24.7), 60.5% males) were enrolled to present the study. Appling GLIM criteria by considering the calf circumference < 31 cm in both genders or mid-upper arm (MUAC) < 23 cm in males and MUAC < 22 cm in females as reduced muscle mass had an appropriate accuracy (84.6%, 83.4%, respectively), good ability to distinguish malnourished patients (AUC ROC: 0.85, 0.83, respectively), satisfactory sensitivity (89.58%, 84.02%, respectively), and satisfactory specificity (81%, 83%, respectively) compared to the SGA tool. Furthermore, the reliability of the GLIM criteria for malnutrition diagnosis in hospitalized patients was acceptable in all 3 applied approaches (KR-20 > 0.5). The malnutrition diagnosed by GLIM criteria could significantly predict the odds of prolonged hospital stays, 30-days hospital readmission, and 60-days mortality, while it had no significant association with the risk of hospital mortality. Conclusion: The current study revealed that applying GLIM criteria had satisfactory validity in diagnosing hospital malnutrition in non-critically ill hospitalized patients.